2010
DOI: 10.1002/chem.201000758
|View full text |Cite
|
Sign up to set email alerts
|

Durability Improvement of a Pt Catalyst with the Use of a Graphitic Carbon Support

Abstract: Graphitic carbon is the key: A Pt catalyst that is supported on carbon nanocages with a graphitic structure is found to exhibit not only a high catalytic activity, but also a superior thermal stability and electrochemical durability in harsh operating conditions when compared with a counterpart that is supported on conventional carbon black (see graphic).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 66 publications
(36 reference statements)
2
20
0
Order By: Relevance
“…Especially the small losses in ECSA for the catalysts with graphitized support (Pt/graph-C) and low surface area supports (Pt/LSA-C I and Pt/LSA-C II) all depict quite good stabilities considering their comparatively small platinum particle sizes, and the initial agglomeration and coalescence due to the very small inter-particle distances as a consequence of their low specific support surface areas. This observation is in good agreement with literature reports that emphasize the positive effect of graphitization on the resistance against carbon corrosion [23,67,84]. The effect of the surface structure of the carbon supports for fuel cell catalysts was demonstrated by Reetz et al [85] in a separate study.…”
Section: Resultssupporting
confidence: 91%
“…Especially the small losses in ECSA for the catalysts with graphitized support (Pt/graph-C) and low surface area supports (Pt/LSA-C I and Pt/LSA-C II) all depict quite good stabilities considering their comparatively small platinum particle sizes, and the initial agglomeration and coalescence due to the very small inter-particle distances as a consequence of their low specific support surface areas. This observation is in good agreement with literature reports that emphasize the positive effect of graphitization on the resistance against carbon corrosion [23,67,84]. The effect of the surface structure of the carbon supports for fuel cell catalysts was demonstrated by Reetz et al [85] in a separate study.…”
Section: Resultssupporting
confidence: 91%
“…In particular, carbon nanotubes, carbon nanofibers, carbon nanohorns, and other carbon nanomaterials have been widely investigated due to their chemical inertness, low background current, relatively wide potential window, high surface area, and good electrical conductivity. Numerous studies have shown that these hybrid materials have a pronounced electrochemical response towards ascorbic acid (AA) [1], dopamine (DA) [2], uric acid (UA) [3], β-nicotinamide adenine dinucleotide (NADH) [4], glucose [5,6], hydrogen peroxide [7,8], and methanol [9][10][11]. Although great progress has been made in the use/application of these carbon nanomaterials, the search for new carbon nanomaterials continues, in order to improve their electrochemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Fundamental understanding and deliberate control of structural and morphological changes of catalytically active metal nanoparticles [1][2][3] under reactive conditions is of general importance for a wide range of reaction processes in heterogeneous and electrochemical catalysis, such as the water-gas shift reaction, [4] NO oxidation, [5] ammonia decomposition, [6] hydrodesulfurization, [7] methanation, [8] oxygen evolution, [9] or the oxygen reduction reaction. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] The long-term durability and-associated with it-the activity of metal-nanoparticle catalysts are controlled by diverse effects pertaining to loss of catalytic surface area, such as particle coalescence, particle agglomeration, or to a loss of active catalytic centers caused by changes in the catalyst structure, by decomposition of catalysts, or by site poisoning. In particular, metal-particle growth is a very common reason of catalyst deactivation leading to reduced catalyst dispersions and metal-atom utilization and hence results in reduced metal-mass-based activity and catalytic active surface area.…”
Section: Introductionmentioning
confidence: 99%